FUNGSI SISTEM PENGENDALIAN INTERN DALAM MENCEGAH KREDIT MACET PADA LEMBAGA PERKREDITAN DESA (STUDI KASUS PADA LPD PAKRAMAN BITERA KABUPATEN GIANYAR) - Ni Nyoman Sudiyani; Anak Agung Putu Gede Bagus Arie Susandy (Juara: Jurnal Riset Akuntansi, 2018)
Village Credit Institution (LPD) is one of the subsystems of financial institutions owned by traditional villages whose activities are engaged in credit, namely collecting funds (passive credit) and channeling funds (active credit) with a certain interest rate. Factors that cause the emergence of bad credit include errors in investment plans, unbalanced cash flow, less predictable economic conditions, natural conditions and company management that do not work according to function. The Internal Control System in the LPD is the LPD Supervisory Board and the principle of credit assessment using 5C analysis, plays an active role in preventing bad credit. This study will discuss how the SPI functions of the Supervisory Board in minimizing bad credit. Based on the results of observations and interviews with Pakraman Bitera LPD management, it can be concluded, that a) 5C credit assessment has been carried out according to the rules applicable in Pakraman Bitera LPD to every prospective debtor who submits an application (credit b) SPI function, namely the Supervisory Board at Pakraman Bitera LPD has been carried out in accordance with the four functions of the Supervisory Board. The occurrence of bad credit at Pakraman Bitera LPD is caused by capital and economic conditions that are still not predictable with certainty. But these policies can still be taken by tackling bad loans through these 5 methods.